2015
DOI: 10.1016/j.pharmthera.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

PIM kinase (and Akt) biology and signaling in tumors

Abstract: The initiation and progression of human cancer is frequently linked to the uncontrolled activation of survival kinases. Two such pro-survival kinases that are commonly amplified in cancer are PIM and Akt. These oncogenic proteins are serine/threonine kinases that regulate tumorigenesis by phosphorylating substrates that control the cell cycle, cellular metabolism, proliferation, and survival. Growing evidence suggests that cross-talk exists between the PIM and Akt kinases, indicating that they control partiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
182
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(186 citation statements)
references
References 114 publications
4
182
0
Order By: Relevance
“…It was reported previously that HCV transiently activates the PI3K-AKT pathway during virus entry (36). Growing evidence suggests that Pim kinases cross talk with PI3K-AKT kinases to produce synergetic effects on cell proliferation and survival signaling pathways (37)(38)(39). Therefore, we are tempted to speculate that Pim kinase might regulate HCV entry by promoting CD81 and claudin-1 receptor complex formation via PI3K-AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 92%
“…It was reported previously that HCV transiently activates the PI3K-AKT pathway during virus entry (36). Growing evidence suggests that Pim kinases cross talk with PI3K-AKT kinases to produce synergetic effects on cell proliferation and survival signaling pathways (37)(38)(39). Therefore, we are tempted to speculate that Pim kinase might regulate HCV entry by promoting CD81 and claudin-1 receptor complex formation via PI3K-AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 92%
“…The provirus integration sites for Moloney murine leukemia virus (PIM) kinases are a highly conserved family of serine/threonine kinases (1,2). The PIM kinase family is composed of 3 different isoforms, PIM-1, PIM-2, and PIM-3, which share high homology at the amino acid sequences (3) and have functional redundancy (4).…”
Section: Introductionmentioning
confidence: 99%
“…An inhibitory effect of PIM-1 silencing on the proliferation of melanoma cells has been previously suggested [3]. SMI-4a is a small molecular highly selective PIM-1 inhibitor that has been found to block PIM-1 kinase activity in vitro and in vivo [14].…”
Section: Discussionmentioning
confidence: 96%
“…A growing body of evidence has demonstrated that atopic expression of PIM-1 in cancer cells is responsible for tumour growth and metastasis [3]. Inhibition of PIM-1 by knockdown studies can reduce proliferation and viability in preclinical models of melanoma [4].…”
Section: Pim-1 Which Belongs To the Pim Family Is -----------------mentioning
confidence: 99%
See 1 more Smart Citation